Peculiarities of Communicative Competence Formation of Future Physical Education Specialists - Tsaryk, Olga; Krychkivska, Oksana (Pedagogical Discourse, 2024)
The article is devoted to the study of the formation of communicative competence of future specialists in physical education and sports, which is an important aspect of their professional training. The purpose of the article is to study the peculiarities of forming the communicative competence of future specialists in physical education and sports. Since effective communication is an integral part of pedagogical, coaching and organisational activities, especially in the context of the dynamic development of physical education, the need to develop communication skills is becoming particularly relevant. The study emphasises that a high level of communication competence requires not only knowledge of teaching and training methods, but also the possession of interpersonal skills that ensure effective interaction, motivation and psychological support for the participants in the process. The article pays special attention to the peculiarities of forming communicative competence in future specialists in physical education and sports. Given the specifics of this profession, the need to integrate theoretical knowledge with practical experience, as well as the importance of adapting to the changing conditions of the training process, communication becomes an important tool for forming effective interaction with different groups - students, athletes, colleagues etc. It is noted that the ability to develop empathy, leadership skills, stress resistance and self-confidence directly affects the effectiveness of communication in the sports environment. The research methods include analysis of scientific sources, comparison and synthesis of the data obtained, which allows to assess the role of communication competence in the professional activities of specialists. It is noted that modern teaching methods, such as role-playing games and situational modelling, play an important role in the development of these skills. In particular, the study demonstrates that the use of interactive methods contributes not only to the development of theoretical knowledge but also to the effective formation of communication skills. It is stated that the study of the peculiarities of the formation of communicative competence is important for improving the effectiveness of professional training of future specialists in physical education and sports, as it directly affects the quality of their activities in sports practice. The article substantiates the need for an integrated approach that combines theoretical knowledge with real practical situations to ensure a high level of communication competence in future coaches and teachers.